2019
DOI: 10.12968/jowc.2019.28.11.784
|View full text |Cite
|
Sign up to set email alerts
|

Barbed suture and glue in skin closure during lower limb arthroplasty: reduced delayed discharge due to wound exudate

Abstract: Objective: The number of hip and knee replacement performed is rising, causing increased pressure for the timely management of these patients. A dry incision is considered a prerequisite for discharge. This is a retrospective cohort study comparing two treatments for skin closure during elective hip and knee arthroplasty. Methods: A barbed monofilament absorbable 3.0 subcuticular suture (Quill), with the additional surface application of n-butyl-2-cyanoacrylate glue, was used for the study group and metal clip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…10,[20][21][22] Roumeliotis and Graham reported that tissue adhesive with subcuticular suture application was a viable option for skin closure after lower limb arthroplasty and can reduce the incidence of prolonged wound discharge. 23 However, their study had several obvious limitations. Firstly, the study was retrospective and two groups of patients came from different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…10,[20][21][22] Roumeliotis and Graham reported that tissue adhesive with subcuticular suture application was a viable option for skin closure after lower limb arthroplasty and can reduce the incidence of prolonged wound discharge. 23 However, their study had several obvious limitations. Firstly, the study was retrospective and two groups of patients came from different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…A British National Health System study on skin closure in hip and knee arthroplasty found a notable reduction in prolonged wound drainage and inpatient stay for wound exudate with the use of barbed suture and glue compared with staples or monofilament suture. 27 They also conducted a cost-benefit analysis which demonstrated overall cost savings with the use of barbed suture, despite the more expensive cost of the suture compared with staples. The extra cost in using barbed suture was outweighed by its benefit in reducing the cost of prolonged inpatient hospitalization for wound observation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot state that the increased LOS is attributable solely to the type of wound closure, the approximate 2-day difference is consistent with previous literature demonstrating a similar delay until postoperative wounds are dry after staple closure. 17 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there were no differences in KSS, ROM, or cosmesis. Likewise, Roumeliotis et al 13 retrospectively evaluated a TJA cohort treated with either a barbed suture versus a conventional method demonstrating a significantly lower incidence of sustained wound drainage (1 vs. 14%, p ¼ 0.05, RR: 10; 95% confidence interval [CI]: 1.31-76.13). Several further studies have supported the proposed advantages of barbed suture regarding closure efficiency and decreased drainage.…”
Section: Subcuticular Tissue/skin Layermentioning
confidence: 99%